(untitled) (Semiárida, 2018)
Currently, in the semiarid Pampa, there is a growing interest by farmers to reintroduce pastures into crop rotations. In response to this demand, the objective was to evaluate the biomass production, quality, and efficiency by pastures of two species with and without nitrogen fertilization in a Mollisol of the semiarid Pampa. The treatments were Fescue-Wheatgrass and Wheatgrass-Lucerne without nutrient contribution (T) and fertilized with nitrogen (F). The design was in completely randomized blocks with 3 replicates.Aerial biomass dry matter, digestibility and protein contents were determined during four growing seasons. Soil moisture content was determined at each date of biomass harvest, and the consumptive water use (UC) and water use efficiency (EUA) were calculated. The results showed that Wheatgrass-Lucerne presented higher production, better quality and no response to fertilization, compared to Fescue-Wheatgrass. In the latter, the response to fertilization was significant, affecting both biomass and protein content. The effect of fertilization in Fescue-Wheatgrass firstly improved the quality and afterwards resulted in higher quantity of fodder produced. The average UC during the 4-year period of both pastures was similar, 781 mm for Fescue - Wheatgrass and 758 mm for Wheatgrass - Lucerne, the average EUA was superior in Wheatgrass - Lucerne (10,4 kg DM.ha-1.year-1 ) compared to Fescue-Wheatgrass (8, 5 kg DM.ha-1 .year -1 ). On average, pasture Fescue - Wheatgrass produced 1.8 and 2.6 kg.ha-1 of protein per day for T and F respectively, while Wheatgrass - Lucerne presented values of 2.8 and 3.1 kg.ha-1 of protein per day for T and F, respectively. DOI: http://dx.doi.org/10.19137/semiarida.2017(01).19-25